Urgensi Program Gerakan 1821 dalam Menumbuhkan Keaktifan Belajar Santri di Pondok Pesantren Rochmatul Maula Desa Latukan Karanggeneng Lamongan - Askhabul Kirom (Kuttab : Jurnal Ilmu Pendidikan Islam, 2019)
In the age of globalization like today, rapid technological developments have resulted in less interaction between family members, friends, and neighbors, indifference have resulted. Hence the government of the latdvillage adopted a clever program of my village’s 1821 movement that hopefully cement social ties with families and neighborhoods. From the background above, researchers gleaned about [1] How is The Urgency of the 1821 Movement Program in Growing Student Learning Activities in the Rochmatul Maula Islamic Boarding School in Latukan Village Karanggeneng Lamongan [2] What are the supporting and inhibiting factors of the urgency of the 1821 movement program in Growing Student Learning Activities in the Rochmatul Maula Islamic Boarding School in Latukan Village Karanggeneng Lamongan [3] What is the solution to the inhibitory factor of the 1821 movement program in Growing Student Learning Activities in the Rochmatul Maula Islamic Boarding School in Latukan Village Karanggeneng Lamongan. In this study, researchers descriptive qualitative research methods, with interviews, observation, and documentation. The results of this study include: 1) The 1821 movement program is very important in building family harmony, reducing dependence on gadgets an TV, and students are more active in learning, 2) The village government and also the Islamic boarding school have provided facilities such as forming a task force and providing a comfortable place to study, and what is hindering is the lack of awareness of residents of the benefits of the 1821 movement program, 3)  Approaching citizens and providing information on the importance of the 1821 movement program.